A non-catalytic role of DNA polymerase η in recruiting Rad18 and promoting PCNA monoubiquitination at stalled replication forks - Durando, Michael (Oxford University Press, 2013)
Trans-lesion DNA synthesis (TLS) is a DNA damage-tolerance mechanism that uses low-fidelity DNA polymerases to replicate damaged DNA. The inherited cancer-propensity syndrome xeroderma pigmentosum variant (XPV) results from error-prone TLS of UV-damaged DNA. TLS is initiated when the Rad6/Rad18 complex monoubiquitinates proliferating cell nuclear antigen (PCNA), but the basis for recruitment of Rad18 to PCNA is not completely understood. Here, we show that Rad18 is targeted to PCNA by DNA polymerase eta (Polη), the XPV gene product that is mutated in XPV patients. The C-terminal domain of Polη binds to both Rad18 and PCNA and promotes PCNA monoubiquitination, a function unique to Polη among Y-family TLS polymerases and dissociable from its catalytic activity. Importantly, XPV cells expressing full-length catalytically-inactive Polη exhibit increased recruitment of other error-prone TLS polymerases (Polκ and Polι) after UV irradiation. These results define a novel non-catalytic role for Polη in promoting PCNA monoubiquitination and provide a new potential mechanism for mutagenesis and genome instability in XPV individuals.